International trade structure and analysis of complementarity between China and Poland, the Czech republic and Hungary - Zheng, Xiaosong; Zhang, Linfeng; Chen, Ruilin; Jia, Lijun (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The purpose of the article is to study the current international trade structure and complementarity between China and the three main central European countries: Poland, the Czech Republic, and Hungary. Based on the international trade structure study, trade complementarities are discussed and further development strategies are proposed. In this study some relevant international trade theories are used in the quantitative analyses and these include revealed comparative advantage index (RCA) and trade complementarity index (TCI). At the end of the article a stochastic frontier trade gravity model is used to calculate trade efficiency and potential between China and the three central European countries. It is found that complementarities of China to the three central European countries are mainly in the labour-intensive products, while complementarities of the three central European countries to China are in the resource-intensive products. However, the current structure of imported and exported products between China and the three central European countries is different from results of the complementarity analyses. At the end of the article some development strategies are proposed to optimize the international trade structure between China and the three central European countries
Argumenta Oeconomica, 2019, Nr 2 (43), s. 39-65
Keywords: international trade; structure; complementarity; China; CEEC